Natural Hazards : Earthquakes, Volcanoes, and Landslides - Singh, Ramesh; Bartlett, Darius; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
This book addresses relevant aspects of earthquakes, volcanoes, and landslides from a scientific and applied engineering perspective. It aims to provide information on the physics and physical processes, indicators, monitoring, mitigation, and geology of these natural hazards. The book highlights the current state of research on these hazards, and deals primarily with their understanding, monitoring and prediction. There is emphasis on satellite monitoring and remote sensing technology used in prediction and assessments. The chapters presented in the book intend to stimulate thinking and further research in the field of natural hazards disaster management.
Gujarat Earthquake: Ground Deformation.----M. G. Thakkar -- Gujarat Earthquake: Liquefaction.----M. G. Thakkar -- Earthquakes and Medical Complications.----Scarlet Benson, Laura Ebbeling, Michael J. VanRooyen and Susan A. Bartels -- Utilization of satellite geophysical data as precursors for earthquake monitoring.----T. J. Majumdar -- Satellite radar imaging and its application to natural hazards.----Matt E. Pritchard and Sang-Ho Yun -- DEMETER Satellite and Detection of Earthquake Signals.----Michel Parrot -- TIR Anomaly as Earthquake Precursor.----Luca Piroddi -- Stress Change and earthquake triggering by reservoirs: role of fluids.----Kalpna Gahalaut -- Earthquake Precursory Studies in India: An Integrated Approach.Geomorphic Features Associated with Erosion. -- Brijesh K. Bansal and Mithila Verma -- Geomorphic Features Associated with Erosion----Niki Evelpidou, Isidoros Kampolis and Anna Karkani -- Thar Desert: Source for Dust Storm.----Priyabrata Santra, Suresh Kumar and M. M. Roy -- Coastal Subsidence: Causes, Mapping, and Monitoring.----Andrea Taramelli, Ciro Manzo, Emiliana Valentini and Loreta Cornacchia -- Subsidence Mapping Using InSAR.Earthquakes and Associated Landslides in Pakistan.----Mukesh Gupta -- Landslides in Jamaica: Distribution, Cause, Impact and Management.----Servel Miller, Anestoria Shalkowski, Norman Harris, Dionne Richards -- and Lyndon Brown -- Landslides: Causes, Mapping, and Monitoring: Examples from Malaysia.----Omar F. Althuwaynee and Biswajeet Pradhan -- Mapping and Monitoring of Landslides Using LiDAR. -- Michel Jaboyedoff, Antonio Abelln, Dario Carrea, Marc-Henri Derron, Battista Matasci and Clment Michoud -- Radar Monitoring of Volcanic Activities----Zhong Lu and Daniel Dzurisin -- Active Volcanoes: Satellite Remote Sensing.----Nicola Pergola, Eugenio Sansosti and Francesco Marchese -- Application of Thermal Remote Sensing to the Observation of Natural Hazards.----Matthew Blackett.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Civil / Earthquake; SOCIAL SCIENCE / Disasters & Disaster Relief; DEMETER, Remote sensing, ionosphere; Earthquakes, indicators, monitoring, geology; Landslide, GIS, Modeling; LIDAR, laser scanning, landslides; Underground water, lava flows, eruption plumes, ash clouds, radar interferometry; Natural disasters; BUSINESS & ECONOMICS / Infrastructure; SOCIAL SCIENCE / General; Electronic books